IPTEKS PERNYATAAN STANDAR AKUNTANSI PEMERINTAHAN NO 07 PADA BADAN KEPEGAWAIAN, PENDIDIKAN DAN PELATIHAN KOTA MANADO - Waworundeng, Aryani K; Onibala, Tesalonika; Latjandu, Lady (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2018)
Pernyataan Standar Akuntansi Pemerintahan No. 07" is a standard who control about fixed assets. The scope of this standard is applied to every unit of government who report their financial statement and sets about their accounting treatments. "Badan Kepegawaian, Pendidikan, dan Pelatihan Kota Manado" duty is to help the government organize some part of government's matter in regional civil servant's management and take responsibility in financial management as an accounting entity, must carry out their duty for budget's utilization. Based on the treatment applied, result shows that recognition, measurement, disclosure, depreciation, termination and elimination already match with "Peraturan Pemerintah Nomor 71 Tahun 2010" about "Pernyataan Standar Akuntansi Pemerintah No. 07 Akuntansi Aset Tetap", but for termination and elimination of fixed assets didn't completely match with "Standar Akuntansi Pemerintahan.Keywords: fixed assets, PSAP No. 07